Naloxone as a trigger to identify opioid-related adverse events in pediatric intensive care units - Haline Ogata; Fábio A. Motta; Marinei C. Ricier (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Objective: this study had the objective to identify opioid-related Adverse Drug Events (ADE) with naloxone as a trigger and evaluate the patterns of naloxone administration in hospitalized children as well as verify the report of these ADE to the hospital's pharmacovigilance department. Methods: a retrospective review of electronic medical records was conducted with records of pediatric patients who received naloxone from January 1st, 2015 to June 30th, 2016. Descriptive statistics and analysis of Variance (ANOVA) followed by Tukey's test were performed to analyze the results (P < 0.05 was considered statistically significant). The study was conducted in a tertiary children's hospital in Paraná, Brazil. Results: we found 58 opioid-related ADE (3.2 events/month) and an underreporting rate of 93% at the hospital. All of the events occurred in Intensive Care Units (ICU) while most of the patients were female (51.7%) and infants (from 1 month old to 24 months old) (51.7%) inside the Cardiac ICU (63.8%). Fentanyl was the most prescribed opioid (66.2%); apnea (29.31%) and insaturation (20.69%) were the most reported symptoms during the ADE. All opioid-related ADEs caused temporary harm to the patients and required intervention. However, only 2.8% of the patients presented ADE by opioid intoxication. The opioid-related ADE were not influenced by opioid types, age groups or patients' diseases. Conclusions: these findings showed a higher incidence of opioid-related ADE inside the Cardiac ICU among infants and a significant underreporting rate of these ADE to the pharmacovigilance department. Our study strengthens the importance of the human factor as a possible cause of ADE in pediatric patients, as well as the challenge to manage patient's safety in pediatric institutions.